Financial inclusion: What's it worth? - Miguel Ampudia; Michael Ehrmann (Bank of Canada, 2016)
The paper studies the determinants of being unbanked in the euro area and the United States as well as the effects of being unbanked on wealth accumulation. Based on household-level data from The Eurosystem Household Finance and Consumption Survey and the U.S. Survey of Consumer Finances, it first documents that there are, respectively, 3.6 per cent and 7.5 per cent of unbanked households in the two economies. Low-income households, unemployed households and those with a poor education are the most likely to be affected, remarkably more so in the United States than in the euro area. At the same time, there is a role for government policies in fostering financial inclusion. Using a propensity score matching approach to estimate the effects of being unbanked, we found that banked households report substantially higher net wealth than their unbanked counterparts, with a gap of around exteuro74,000 for the euro area and 42,000 for the United States. A potential reason for this wealth difference is that banked households are considerably more likely to accumulate wealth through ownership of their principal residence.
Keywords: G21; G28; D14; 330; Econometric and statistical methods; Financial services; Financial system regulation and policies; Housing